Protocolos assistenciais em ginecologia em maternidade terciária de Fortaleza, CE - Arruda, Pâmela Mendes (2022)
Clinical protocols are technologies that are part of the organization of work and constitute an important health management tool. The objective of this study was to elaborate, update and edit the Clinical Protocols in Gynecology to be adopted by the Maternity School Assis Chateaubriand - Federal University of Ceará (MEAC/UFC). An integrative literature review was carried out in order to identify, analyze and synthesize, in the format of clinical protocols the evidence-based recommendations available for each defined topic. In total, 44 protocols were listed to compose the institution's book of Clinical Protocols in Gynecology, of which six were selected to acquire the multiprofessional format. The elaboration stages included: updating and elaboration of new protocols, review by the editors, internal validation, publication on the MEAC website and production of the digital and printed book. The protocol construction process is highly complex and must be carried out with methodological rigor, in order to guarantee its credibility. There is a great variety of methodologies used and it is necessary to expand the discussion in the literature on elaboration strategies, mainly involving multidisciplinary protocols. At the end of our process, twenty-one protocols were updated, of which two acquired the multiprofessional format. Nine new protocols were developed, two of them multiprofissional. In total, thirty-seven protocols will compose the book Clinical Protocols in Gynecology by MEAC.